Attitude of Nursing Students towards LGBTIQ Individual and its Associated Factors in Kathmandu Metropolitan City - Dangi, Sabita; Bist, Amrit; Acharya, Aashish (Journal of Public Health International, 2023)
Background People may have both negative and positive attitudes about other people, their way of living and those attitudes can be influenced by various factors. LGBTIQ individuals are facing various difficulties and barriers to run their daily life due to different attitudes of people. Attitudes may be different from person to person influenced by their knowledge, acceptance behaviour and understanding. By finding out the associated factors that influences the attitude of people we can change people’s view towards LGBTIQ individuals. Each and every person deserves to be treated equally regardless of their gender, sexual orientation, and preferences. Methods This was a cross-sectional study in which the sample size was 423 and the study population was nursing students. A simple random sampling method was used to select sample for the study. Self-administered questionnaire was used to collect data. The collected data was entered in EPI 3.1 and analyzed using SPSS 25. A descriptive statistic was used to find out the frequency and percentage and analysis (chi-square) was used to find out the association between the dependent and independent variables. A p-value of <0.05 was considered statistically significant. Results Results showed that 87.2% have positive attitudes towards LGBTIQ individuals, and the majority (56.6%) have knowledge about homosexuality. Similarly, more than two-thirds (82.7%) of respondents were not homophobic, and 50.4% showed positive stereotypes about LGBTIQ individuals. Religion (p=0.030), caste (p=0.001) and Family type (p=0.016) were statistically significant with regard to the attitudes of students towards LGBTIQ. Conclusion The majority of students had positive attitudes towards LGBTIQ individuals and few had negative attitudes. Almost half of the respondents had adequate knowledge about homosexuality. The majority of students were not homophobic and few were homophobic. Half had positive stereotypes and about other half had negative stereotypes.
Keywords: Associated factors; Attitude; LGBTIQ; Nursing Students